The Balance Of Legal Position Of Farmers With Dairy- Producing Industries In The Contents Of Milk Deposit Contracts At KUD - Widaningsih, Widaningsih; Suhariningsih, Suhariningsih; Sihabuddin, Sihabuddin; Santoso, Budi (Technium Social Sciences Journal, 2023)
The development of contract law gave birth to the principle of balance which states that a contract is binding as long as it is based on a balance of interests between the parties. The agreement is based on the terms of the validity of the agreement. The types of research are normative law, statutory approach and case approach. In conclusion, the contents of the contract on milk deposit at the KUD contain an agreement between the farmer and the milk-producing industry. In making a contract, the parties should have a balanced position, if they do not have a balanced position, it is possible that one party will dominate the other party. In the farmer’s contract with the milk-producing industry, at the beginning of the contract (pre-contract) it appears that the bargaining position of the parties is balanced. If we look closely at the contents of the contract, there is an imbalance of position. The principle of balance has not been implemented properly, but the application of the principle of balance is indirectly contained in Article 1320 of the Civil Code, namely agreements, implementation in good faith and binding agreements with propriety, custom and law. Shows that in an agreement there should be a balance between the parties so as to create a sense of justice. An unbalanced contract has no binding force because it is contrary to good faith, a sense of justice, and propriety. As a result, an unbalanced agreement can be requested to cancel the agreement.